Spatial Working Memory in Male Rats: Pre-Experience and Task Dependent Roles of Dopamine D1- and D2-Like Receptors - Bezu, Mekite; Maliković, Jovana; Kristofova, Martina; Engidawork, Ephrem; Höger, Harald; Lubec, Gert; Korz, Volker (Frontiers in Behavioral Neuroscience, 2017)
The dopaminergic system is known to be involved in working memory processed by several brain regions like prefrontal cortex, hippocampus, striatum. In an earlier study we could show that Levodopa but not Modafinil enhanced working memory in a T-maze only during the early phase of training (day 3), whereas the later phase remained unaffected. Rats treated with a higher dose performed better than low dose treated rats. Here we could more specifically segregate the contributions of dopamine type 1- and 2- like receptors (D1R; D2R) to the training state dependent modulation of spatial working memory by intracerebroventricular application of a D1R-like (SKF81297) and D2R-like agonist (Sumanirole) and antagonist (SCH23390, Remoxipride) at a low and high dose through 3 days of training. The D1R-like-agonist at both doses enhanced working memory at day 1 but only in the low dose treated rats enhancement persists over training compared to control rats. Rats treated with a high dose of a D1R-like-antagonist show persistent enhancement of working memory over training, whereas in low dose treated rats no statistical difference at any time point could be determined compared to controls. The D2R-like-agonist at both doses does not show an effect at any time point when compared to control animals, whereas the D2R-like antagonist at a low dose enhanced working memory at day 2. For the most effective D1R-like agonist, we repeated the experiments in a water maze working memory task, to test for task dependent differences in working memory modulations. Treated rats at both doses did not differ as compared to controls, but the temporal behavioral performance of all groups was different compared to T-maze trained rats. The results are in line with the view that spatial working memory is optimized within a limited range of dopaminergic transmission, however suggest that these ranges vary during spatial training.